Kedudukan Hukum Alas Hak Sebagai Alat Bukti Kepemilikan terhadap Tanah Masyarakat Perspektif Wahbah Az-Zuhaili: - Wahyuni Nasution Nasution; Tetty Marlina Tarigan (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
The problem in this study is regarding the status and legitimacy of the rights described by the land certificate as proof of land ownership. Residents of Tanjung Marulak Hamlet are legally entitled to receive a statement letter from the Regent alias SK-Regent as proof of ownership of their property. Land Certificate (SKT) is a written document owned by a private person who owns a piece of land but has not been certified; the weight of proof does not show the authenticity of the deed. In Indonesia, there are still many people who believe that land certificates have the same legal weight as other certificates, especially in Dusun Tanjung Marulak. The purpose of this study is to determine the position and legitimacy of rights to land certificates as proof of land ownership in the land law system. Researchers used normative legal research in this study which was supplemented by interviews. According to the current law, this investigation investigates and analyzes primary data and secondary data. Literature research in the library and field research in the field were both used to collect all data. This research is qualitative in nature. Based on the research results, the Land Certificate issued by the Regent of Tanjung Marulak Hamlet through Excerpt of Letter Number 69/DA/HML/LB/1980 is legal proof of land ownership. Keywords: Ownership, Land Certiface, Wahbah Az-Zuhaili